THE ADAMITES: TOPOI - FICTION - REALITY? - Čornej, Petr (Bohemica Olomucensia, 2021)
For several centuries, scholars have been debating whether the Hussite Adamites really worshipped ritual nudism and free love in the remote corners of the South Bohemian Nežárka River, or whether this was merely a slander aimed at discrediting the so-called Picards, who denied the presence of Christ in the sacrament of the altar and rejected the priest's prerogative. For Catholics and for most Hussites, these views were totally unacceptable, since they denigrated one of the central sacraments (the reception of the Eucharist under both ways, of which the chalice was the sign, was considered by the Hussites to be a condition of salvation) and the basic structures of Christian society. On the basis of a re-analysis of key texts, the study confirms the earlier finding that the so-called Adamite group broke away in the spring of 1421 from the persecuted community, originally centred around the Tábor priests Martin Húska and Petr Kánisz. Soon it found refuge on still unlocalized "island" between Veselí nad Lužnicí and Stráž nad Nežárkou, and here (in an isolated place) it lived according to its own principles. Whether the community here restored the paradisiacal state in which no human action is sinful, following the example of Adam and Eve, cannot be said with certainty. The testimonies of the leading Hussite thinkers Jakoubek of Stříbro and especially the well-informed Petr Chelčický do not speak of ritual nudism or sexual extravagance, but of free sexual relations in conjunction with the blasphemy of the sacrament of the altar, The South Bohemian sources supplement this picture with reports of armed raids by so-called adamites or adamians (Old Czech used the term naháči for them, only later the names adámkové, adamci, resp. adamici), who - in an attempt to make a living - robbed and killed the inhabitants of nearby villages and towns. Their propensity for violence completely precludes their identification with the strictly pacifist Waldensian sect. It was their violent actions, together with their heresy, that were the main reason why the Hussite governor Jan Žižka, in cooperation with the surrounding nobles, came out against them and physically exterminated the entire group of several dozen people in October 1421.In an attempt to discourage the population from following the liquidated sectarians, Catholic and Hussite propaganda spread blatant lies about the Adamites (they were said to be incestuous and paedophilic and to deny all Christian principles), drawing on a reservoir of inquisition protocols and older literary topoi. To make it easier to remember, some of the slanders were rhymed into simple verse. Some of these slanders made their way into historiographical texts (the Old Czech Annals, the Verse Annals, the Czech Chronicle of Václav Hájek of Libočany) and were also introduced to Europe through the Historia Bohemica by the Italian humanist Eney Silvio Piccolomini. The original Adamite story, in which reality and fiction were intertwined from the beginning, was gradually fictionalized over the decades. The role of the sect's leader is played either by Adam, a Frenchman endowed with magical skills, or by Rohan, a valiant Czech blacksmith. In 1524, the Franciscan Jan Vodňanský-Aequensis went the furthest in the direction of episodization and fictionalization, enriching the Adamite story in his Locustarium with a number of stories drawn from legend and fiction (the sect leader's companion is the beautiful but barren Mary, a counterpart of the warrior Amazons). Adamite history, shrouded in ambiguity from the start and suffused with a tantalising erotic haze, slowly transformed into an attractive read, combining entertaining elements with a necessary moral mission. Almost all Hussite and Catholic authors were united in the conviction that the terrible Adamite heresy could not have originated in an ethnically Bohemian, deeply religious environment, but was the result of foreign influences, whether English, French, German or Austrian. The lesson of the Adamite history was obvious: if Czech society is to maintain stability, it must not lose its caution against foreigners and at the same time be able to take action against extremists.
Keywords: Hussitism; Picards; heresy; nudity; free love; island; historiography; fiction; abroad